Gog and Magog in literary reception history: the persistence of the fantastic - Swindell, Anthony C. (Journal of the bible and its reception, 2016)
Of all biblical topoi within the repertoire of Western culture, the Gog and Magog narratives have a presence in literary reception history that far outweighs their slender beginnings. They tend also to be an alien element in the metanarratives in which they occur. Even in their earliest biblical manifestation, the ‘Go’ narratives seem to have been grafted onto an existing text. Almost always, their use implies the recovery of the archaic as a means of replenishing or revitalizing present culture. At the same time they persistently signal the phenomenon of the unassimilable in human experience. The topos of Gog of the land of Magog in Ezekiel 38–39 modulates into the twin apocalyptic figures of Gog and Magog of Revelation 20:8–9. Later they become part of the conceptualization of the cultural Other, the uncivilized hordes which must be kept at bay. In European literature they assume a plastic form as representations of what is excluded from culture. In British literature (with which we will be chiefly concerned) they occupy an ambiguous position as figures of the defeated paganism which Christianity has replaced and yet as symbols of a hopeful or whimsical alterity which resists the language, the hegemonic discourse, of the status quo.